The Effects of Metacognitive Strategy Instruction and Self-efficacy on Students Listening Achievement - Kurniawati, K. (LINGUA: Jurnal Bahasa dan Sastra, 2014)
Listening is a demanding skill for the EFL learners and it often demotivates them to learn English. Therefore, the writer was interested in doing an experimental research on listening. This study aimed at investigating (1) a significant interaction effect of Metacognitive Strategy Instruction (MSI) and self-efficacy (SE) on listening achievement (LA) of the students, (2) a significant difference in the students LA after being taught by using MSI, and (3) how much each aspect of listening contributed to the students LA. Purposive sampling technique was used to determine 50 samples from 100 students. The data were analyzed by using twoway anova, paired sample t-test, independent t-test and stepwise regression. The results showed that (1) there was no significant interaction effect of MSI and SE on LA of the students who were taught by using MSI, (2) there was a significant effect in LA of the students scores in pre- and posttest within group after being taught by using MSI. The independent t-test analyses resulted a significant mean difference of LA (14.400, t-value 6.707, (3) the aspects of Ability to Discriminate between Distinctive Sounds contributed 40%, Recognizing Keywords 21.6%, Main Ideas 13.3%, Inference 13.1%, and Identifying Details 12.1%, to the students LA. In conclusion, MSI significantly affected LA of the students without being moderated by SE.